Pseudomonas aeruginosa Positivity and Sensitivity in Invasive Bloodstream Infections Using Automated Bactec in Tertiary Care Teaching Hospital of North India: A Prospective Observational Study - Pankaj Katoch; Vipin Roach (Emerging Trends in Disease and Health Research Vol. 2, 2022)
Background: Pseudomonas aeruginosa is one of the most commonly encountered gram-negative aerobic bacilli in the differential diagnosis of several probable hospital-acquired infections. In bloodstream infections (BSIs) mortality due to Pseudomonas aeruginosa remains an issue of serious concern. The present study is designed to determine the Pseudomonas positivity and sensitivity in Invasive bloodstream infections using automated Bactec systems as the Antibiotic Sensitivity Profiles differ from one clinical setting to another. Material and Methods: All the blood culture samples received in the Department of Microbiology for culture by Bactec Bd fx from July 2015 to June 2016 were included in the study. The blood culture was observed in the Bactec bd fx system for at least 5 days before they are reported as sterile. Results: Among the total 1275 cultures which were positive for bacteria, 931(73.02%) were positive for gram-negative bacteria. Among the total of 931culture which were positive for gram- negative bacteria, Pseudomonas aeruginosa was isolated in 120(12.89%) cultures. Maximum was Pseudomonas spp isolates were 100.00% sensitive to Colistin followed by Levofloxacin 84.44%, Piperacillin Tazobactum 82.50%, PB 77.50%, Amikacin 75.00%, Cefepime 75.00% while Pseudomonas spp isolates were 90% resistant to Ampicillin followed by Ceftazidime clavulanic acid 82.64% and Aztreonam 70.31%. Conclusion: Pseudomonas aeruginosa is one of the most common organisms among Gram- Negative isolates and the most commonly isolated in the neonate and infant age group. All the Pseudomonas isolates showed maximum sensitivity to Colistin followed by Levofloxacin, Piperacillin Tazobactum, Amikacin while they were most resistant to Ampicillin followed by Ceftazidime clavulanic acid and Aztreonam. Some alternative novel techniques need to be developed to counter the increasing menace of antibiotic resistance in this particular pathogenic bacteria.